1996
DOI: 10.1002/(sici)1099-1379(199601)17:1<43::aid-job732>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A field experiment for studying race relations embedded in organizations

Abstract: SummaryWhen social scientists conduct research in organizations, they engage in relationships with respondents in order to obtain information. For studies of race relations in organizations, questions arise about how researchers take account of their organizational and racial group memberships. This field experiment tests hypotheses derived from embedded intergroup relations theory about the effects of questionnaire administration procedures and race of respondents on response rate, reactions to the research, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Tomaskovic-Devey, Leiter, and Thompson (1994), for example, showed that organization-level mail survey nonresponses were related to properties of organizations (e.g., subsidiary status) as well as to topics of questions (e.g., financial information). In a study of race relations, Alderfer and Tucker (1996), reasoning from embedded intergroup relations theory, demonstrated with a field experiment that response rates, response content, and attitudes toward the study depended on the methods of questionnaire administration. Rogelberg, Luong, Sederberg, and Cristol (2000) found that employees' attitudes about their jobs and supervisors were related to the respondents' anticipated nonresponses on a previewed questionnaire, if the instrument were to be administered by their employing organizations.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Tomaskovic-Devey, Leiter, and Thompson (1994), for example, showed that organization-level mail survey nonresponses were related to properties of organizations (e.g., subsidiary status) as well as to topics of questions (e.g., financial information). In a study of race relations, Alderfer and Tucker (1996), reasoning from embedded intergroup relations theory, demonstrated with a field experiment that response rates, response content, and attitudes toward the study depended on the methods of questionnaire administration. Rogelberg, Luong, Sederberg, and Cristol (2000) found that employees' attitudes about their jobs and supervisors were related to the respondents' anticipated nonresponses on a previewed questionnaire, if the instrument were to be administered by their employing organizations.…”
supporting
confidence: 92%
“…Consequently, one can infer that the questionnaire data were more reliable for less threatening topics and less reliable for more threatening topics. This finding is likely to be general, because respondents seem more likely to avoid-both consciously and unconsciously-answers to questions about which they are more anxious and fearful (Alderfer & Tucker, 1996). These results underline the natural caution experienced consultants have when they hear clients say, "There are no problems."…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…Experts suggest that enhanced rapport and disclosure can be established and cultivated if the interviewer is of the same race/ethnicity as the participant (Krysan & Couper, 2003). Both the participants and interviewer in this study were AA, possibly limiting response bias (Alderfer & Tucker, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Alderfer’s work with his wife Charleen together with Bob and Leota Tucker involved an 8-year collaboration employing a mixed race and mixed gender team to diagnose and consult to race relations in a major U.S. corporation (Alderfer, 1992; Alderfer, 1996; Alderfer, Alderfer, Bell, & Jones, 1992; Alderfer, Alderfer, Tucker, & Tucker, 1980; Alderfer, Tucker, Alderfer, & Tucker, 1988; Alderfer, Tucker, Morgan, & Drasgow, 1983). The published record includes diagnostic methodology, intervention design, and research/evaluation processes all derived explicitly from embedded intergroup relations theory.…”
Section: Clayton Paul Alderfermentioning
confidence: 99%